Analisa Sensitivitas Pada Pengoptimalan Powerflow Untuk Menentukan Pengaruh Variasi Beban Terhadap Stabilitas Sistem - Bagus S, Alfian T; Munir, Misbahul; Pambudi, Wahyu Setyo (BEES: Bulletin of Electrical and Electronics Engineering, 2024)
The electrical power system requires reliability to provide good and stable services. Each area has a variety of load characteristics related to the energy patterns of users in that region. As the solution, optimizing power flow in the interconnected system is necessary to improve reliability, quality, and system stability. This study aims to determine the impact of load variations on system stability. The simulation results indicated that the power flow at bus 1 and bus 2, directly connected to the generator, got stable balance. Specifically, bus 1 had an active power of 144 kW and a reactive power of 102 kVAr, while bus 2 had an active power of 54 kW and a reactive power of 54 kVAr. The comparison of active power with the motor constant of 100%-0% static showed that the highest value at load 1 reached 37.12 kW. Similarly, the comparison of reactive power with a motor constant of 80%–20% for the static constant showed that the highest value, achieved at load 6, was 19.2 kVAr. Thus, the simulation is beneficial to analyze the sensitivity in optimizing power flow within the electrical power system and can serve as a reference for future research.